The Magic Mirror : Dada and Surrealism from a private collection - Cowling, Elizabeth; Royal Scottish Academy, Edinburgh (Edinburgh : Scottish National Gallery of Modern Art, 1988)
Agar, Eileen ; Bellmer, Hans ; Bacon, Francis ; Breton, André ; Burra, Edward ; De Chirico, Giorgio ; Dali, Salvador ; Davies, John ; Delvaux, Paul ; Duchamp, Marcel ; Ernst, Max ; Freud, Lucian ; Gascoyne, David ; Giacometti, Alberto ; Grosz, George ; etc.
The Magic Mirror: Dada and Surrealism from a private collection, Royal Scottish Academy, Edinburgh, 30 July - 4 September 1988
boek